Negative current collector, method for manufacturing the same, electrode sheet, and battery
Patent Information
- Application Number
- CN202510714166.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-05-29
AI Technical Summary
[0004]有鉴于此,本发明致力于提供一种一种负极集流体及其制备方法、极片和电池,以解决现有技术中锂离子电池存在的能量密度不足且内阻较大等问题
[0024](1)本发明的负极集流体的制备方法中先制备得到表面含有羟基的碳纳米管,再制备得到碳纳米管改性后的泡沫聚氨酯,最后以所述碳纳米管改性后的泡沫聚氨酯作为工作电极,将所述工作电极、对电极和参比电极置于含有金属离子的电解液中进行沉积反应,得到表面沉积有金属层的基材。泡沫聚氨酯材料中含有较多的孔隙,制备过程中第二铵盐的加入使得高温后会分解成气体,气体逸出后会在材料中形成较多的孔隙结构,进而提高孔隙率,电池内阻降低的同时,Li有更大的沉积面积,可提高电池循环性能;通过沉积反应沉积更多的金属,同时使用碳纳米管改性聚氨酯,因此可以进一步降低电池内阻。
Smart Images

Figure CN120709380B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy batteries, specifically to a negative electrode current collector and its preparation method, an electrode sheet, and a battery. Background Technology
[0002] Lithium-ion batteries have been widely used due to their advantages such as high specific energy, long cycle life, no memory effect, and low self-discharge rate. Applications in large transportation vehicles such as electric vehicles and electric ships have high requirements for driving range, thus demanding higher energy density from lithium-ion batteries. Lithium metal anodes, with their extremely high theoretical specific capacity (3860 mAh / g) and lowest electrode potential (3.04 V compared to the standard hydrogen electrode), have attracted much attention. However, the harmful growth of lithium dendrites during repeated plating / stripping cycles hinders the practical application of lithium metal anodes. The formation of lithium dendrites consumes some electrolyte, and some lithium dendrites lose contact with the electrode after cycling, becoming dead lithium, reducing the initial coulombic efficiency and shortening battery life.
[0003] Copper foam, due to its light weight and porous structure, offers significant advantages in improving the energy density and rate performance of lithium-ion batteries, making it an important direction for future current collector applications. However, its poor toughness may cause Li dendrites to form on its surface, posing a safety hazard. Therefore, there is an urgent need in this field for a lightweight, highly flexible, porous negative electrode current collector. Summary of the Invention
[0004] In view of this, the present invention aims to provide a negative electrode current collector and its preparation method, an electrode sheet and a battery, so as to solve the problems of insufficient energy density and high internal resistance of lithium-ion batteries in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention is implemented as follows:
[0006] A first aspect of the present invention provides a method for preparing a negative electrode current collector, the method comprising the following steps:
[0007] S1. Carbon nanotubes, borohydride, first ammonium salt and first organic solvent are mixed and subjected to first heating and reflux treatment to obtain the first product;
[0008] S2. The first product, water, hydroxide, oxidant and the first organic solvent are mixed and oxidized to obtain the second product; the second product is filtered, washed and dried to obtain carbon nanotubes with hydroxyl groups on the surface.
[0009] S3. The carbon nanotubes with hydroxyl groups on their surface, isocyanate raw material, glycol, water, and a second organic solvent are mixed and subjected to a second heating and reflux treatment to obtain a third product.
[0010] S4. The third product, polytetrahydrofuran raw material, the second organic solvent, and the second ammonium salt are mixed and polymerized to obtain a precipitate; the precipitate is subjected to a second drying treatment to obtain carbon nanotube modified polyurethane foam.
[0011] S5. Using the carbon nanotube-modified polyurethane foam as the working electrode, the working electrode, the counter electrode, and the reference electrode are placed in an electrolyte containing metal ions to carry out a deposition reaction, thereby obtaining a substrate with a metal layer deposited on its surface. The substrate with the metal layer deposited on its surface is then subjected to a washing treatment and a third drying treatment.
[0012] Optionally, in step S1, the mass ratio of the carbon nanotubes, the borohydride, and the first ammonium salt is (2-10):(0.5-4.5):(0.5-6.5); the amount of the first organic solvent used is 25-125 mL relative to each gram of carbon nanotubes; the borohydride includes at least one of sodium borohydride, potassium borohydride, calcium borohydride, magnesium borohydride, and lithium borohydride; the first ammonium salt includes at least one of ammonium sulfate, ammonium nitrate, ammonium chloride, ammonium bisulfate, ammonium fluoride, ammonium carbonate, and ammonium bicarbonate; the first organic solvent includes at least one of tetrahydrofuran, acetonitrile, formamide, and acetone; optionally, in step S1, the conditions for the first heating reflux treatment include: a heating reflux temperature of 80-100°C and a heating reflux time of 8-16 h.
[0013] Optionally, in step S2, the mass ratio of the first product to the hydroxide is (2-10):(1-9); the amount of the first organic solvent used is 25-125 mL relative to each gram of the first product; the amount of water used is 25-125 mL relative to each gram of the first product; the hydroxide includes at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide; the oxidant includes at least one of hydrogen peroxide, sodium hypochlorite, and sodium peroxide; optionally, in step S2, the conditions for the oxidation reaction include: an oxidation temperature of 20-60°C and an oxidation time of 6-10 h; the washing liquid used in the filtration and washing treatment includes at least one of water, ethanol, and acetone; the conditions for the first drying treatment include: a drying pressure of -0.09 to -0.08 MPa, a drying temperature of 40-80°C, and a drying time of 8-16 h.
[0014] Optionally, in step S3, the mass ratio of the carbon nanotubes containing hydroxyl groups on their surface, the isocyanate raw material, and the diol is (31-93):(2-10):(87-261); the amount of the second organic solvent used is 4-20 mL relative to each gram of the carbon nanotubes containing hydroxyl groups on their surface; the amount of water used is 1-5 mL relative to each gram of the carbon nanotubes containing hydroxyl groups on their surface; the isocyanate raw material includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, and naphthalene 1,5-diisocyanate; the diol includes at least one of ethylene glycol, propylene glycol, and butanediol; the second organic solvent includes at least one of toluene, xylene, and benzene; optionally, in step S3, the conditions for the second heating reflux treatment include: a heating reflux temperature of 100-120°C and a heating reflux time of 4-10 h.
[0015] Optionally, in step S4, the mass ratio of the third product to the polytetrahydrofuran raw material is (10-40):(0.5-5.5); the amount of the second organic solvent used is 1-4 mL relative to each gram of the third product; the polytetrahydrofuran raw material includes at least one of polytetrahydrofuran, poly-2-methyltetrahydrofuran, and poly-2-ethyltetrahydrofuran; the second ammonium salt includes at least one of ammonium bicarbonate, ammonium chloride, and ammonium carbonate; optionally, in step S4, the polymerization reaction conditions include: a polymerization temperature of 80-120°C and a polymerization time of 8-16 h; the second drying treatment conditions include: a drying pressure of -0.09 to -0.08 MPa, a drying temperature of 40-80°C, and a drying time of 10-16 h.
[0016] Optionally, in step S5, the counter electrode is a platinum sheet; the reference electrode is Ag / AgCl; the concentration of the metal ions in the electrolyte containing metal ions is 0.1–0.9 mol / L; optionally, the metal ions are copper ions; optionally, in step S5, the deposition treatment conditions include: a constant potential of -1.5 to -0.7 V and a deposition time of 5–15 min; the washing solution used in the washing treatment includes anhydrous ethanol; the conditions for the third drying treatment include: a drying pressure of -0.09 to -0.08 MPa, a drying temperature of 25–45 °C, and a drying time of 8–16 h.
[0017] A second aspect of the present invention provides a negative electrode current collector, which is prepared according to the method described above;
[0018] The negative electrode current collector includes a porous substrate and a metal layer, wherein the metal layer is disposed on the surface and within the pores of the porous substrate;
[0019] The substrate material includes carbon nanotubes with hydroxyl groups on their surface and polyurethane foam; the carbon nanotubes with hydroxyl groups on their surface and the polyurethane foam are connected by hydrogen bonds.
[0020] Optionally, in the substrate, the mass ratio of the carbon nanotubes with hydroxyl groups on the surface to the polyurethane foam is (0.02-0.1):1; the mass ratio of the substrate to the metal layer is 1:0.2-1; the thickness of the substrate is 0.004-0.12 mm; the thickness of the metal layer is 0.5-10 μm; optionally, the material of the metal layer includes copper.
[0021] A third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative current collector prepared according to the preparation method described above, or the negative current collector described above.
[0022] A fourth aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode is the negative electrode described above.
[0023] The beneficial technical effects of the present invention through the above technical solution are as follows:
[0024] (1) In the preparation method of the negative electrode current collector of the present invention, carbon nanotubes with hydroxyl groups on the surface are first prepared, and then carbon nanotube-modified polyurethane foam is prepared. Finally, the carbon nanotube-modified polyurethane foam is used as the working electrode, and the working electrode, counter electrode and reference electrode are placed in an electrolyte containing metal ions to carry out a deposition reaction to obtain a substrate with a metal layer deposited on the surface. The polyurethane foam material contains a lot of pores. During the preparation process, the addition of the second ammonium salt will decompose into gas at high temperature. After the gas escapes, it will form more pore structures in the material, thereby increasing the porosity. While reducing the internal resistance of the battery, Li has a larger deposition area, which can improve the battery cycle performance. More metal is deposited through the deposition reaction, and carbon nanotube-modified polyurethane is used, so the internal resistance of the battery can be further reduced.
[0025] (2) The negative electrode current collector of the present invention is a porous and lightweight foamed copper material, which can reduce the weight of the negative electrode sheet and thus improve the energy density of the battery. Applying the negative electrode current collector of the present invention to the battery can reduce the internal resistance of the battery, enhance the cycle performance of the battery, and reduce the safety risks of the battery.
[0026] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0027] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0028] Figure 1 The diagram shown is a schematic of the negative electrode current collector of the present invention.
[0029] Explanation of reference numerals in the attached figures
[0030] 1: Metal layer;
[0031] 2: Porous substrate. Detailed Implementation
[0032] This invention discloses a negative electrode current collector and its preparation method, as well as an electrode sheet and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0033] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0034] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0035] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0036] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0037] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0038] To address the problems of insufficient energy density and high internal resistance in existing lithium-ion batteries, the present invention adopts the following technical solution:
[0039] A first aspect of the present invention provides a method for preparing a negative electrode current collector, the method comprising the following steps:
[0040] S1. Carbon nanotubes, borohydride, first ammonium salt and first organic solvent are mixed and subjected to first heating and reflux treatment to obtain the first product;
[0041] S2. The first product, water, hydroxide, oxidant and the first organic solvent are mixed and oxidized to obtain the second product; the second product is filtered, washed and dried to obtain carbon nanotubes with hydroxyl groups on the surface.
[0042] S3. The carbon nanotubes with hydroxyl groups on their surface, isocyanate raw material, glycol, water, and a second organic solvent are mixed and subjected to a second heating and reflux treatment to obtain a third product.
[0043] S4. The third product, polytetrahydrofuran raw material, the second organic solvent, and the second ammonium salt are mixed and polymerized to obtain a precipitate; the precipitate is subjected to a second drying treatment to obtain carbon nanotube modified polyurethane foam.
[0044] S5. Using the carbon nanotube-modified polyurethane foam as the working electrode, the working electrode, the counter electrode, and the reference electrode are placed in an electrolyte containing metal ions to carry out a deposition reaction, thereby obtaining a substrate with a metal layer deposited on its surface. The substrate with the metal layer deposited on its surface is then subjected to a washing treatment and a third drying treatment.
[0045] In the preparation method of the negative electrode current collector of the present invention, carbon nanotubes with hydroxyl groups on their surface are first prepared, followed by the preparation of carbon nanotube-modified polyurethane foam. Finally, the carbon nanotube-modified polyurethane foam is used as the working electrode, and the working electrode, counter electrode, and reference electrode are placed in an electrolyte containing metal ions for a deposition reaction to obtain a substrate with a metal layer deposited on its surface. The polyurethane foam material contains a large number of pores. During the preparation process, the addition of the second ammonium salt causes it to decompose into gas at high temperatures. The escaped gas forms a larger porous structure in the material, thereby increasing the porosity. This reduces the battery's internal resistance while providing a larger deposition area for Li, improving battery cycle performance. Furthermore, the deposition reaction deposits more metal, and the use of carbon nanotube-modified polyurethane further reduces the battery's internal resistance.
[0046] In this invention, insufficient carbon nanotubes may lead to insufficient conductivity of the foil; excessive carbon nanotubes may cause agglomeration, thereby reducing the conductivity of the foil. As one embodiment of this invention, in step S1, the mass ratio of the carbon nanotubes, the borohydride, and the first ammonium salt can be (2-10):(0.5-4.5):(0.5-6.5). Exemplarily, the mass ratio of the carbon nanotubes, the borohydride, and the first ammonium salt can be any value from 1:0.25:0.25, 1:2.25:0.25, 1:0.25:3.25, 1:2.25:3.25, 1:0.05:0.05, and 1:0.45:0.65, or any value within the range formed by any two of the above values.
[0047] According to the present invention, if the amount of the first organic solvent is too large, the reaction rate may be slowed down; if the amount of the first organic solvent is too small, the carbon nanotubes may aggregate, increasing the product resistance. In embodiments of the present invention, the amount of the first organic solvent relative to each gram of carbon nanotubes can be 25 to 125 mL. Exemplarily, the amount of the first organic solvent relative to each gram of carbon nanotubes can be any value selected from 25 mL, 50 mL, 75 mL, 100 mL, and 125 mL, or any value within the range formed by any pair of the above values.
[0048] For example, the borohydride may include at least one of sodium borohydride, potassium borohydride, calcium borohydride, magnesium borohydride, and lithium borohydride.
[0049] For example, the first ammonium salt may include at least one of ammonium sulfate, ammonium nitrate, ammonium chloride, ammonium bisulfate, ammonium fluoride, ammonium carbonate, and ammonium bicarbonate.
[0050] For example, the first organic solvent may include at least one of tetrahydrofuran, acetonitrile, formamide and acetone.
[0051] In some embodiments, the conditions for the first heating reflux treatment in step S1 may include: a heating reflux temperature of 80–100°C and a heating reflux time of 8–16 h. As an example, the temperature of the first heating reflux treatment may be 80°C, 85°C, 90°C, 95°C, 100°C, etc., and the time of the first heating reflux treatment may be 8 h, 10 h, 12 h, 14 h, 16 h, etc.
[0052] In one embodiment of the present invention, in step S2, if the amount of hydroxide is too large, the reaction rate may slow down; if the amount of hydroxide is too small, the reaction product may be affected (low surface -OH content). In some embodiments, the mass ratio of the first product to the hydroxide can be (2-10):(1-9). Exemplarily, the mass ratio of the first product to the hydroxide can be any value among 2:1, 1:1, 1:2, 1:4.5, and 10:9, or any value within the range of any two of the above values.
[0053] According to the present invention, in step S2, if the amount of the first organic solvent is too large, the reaction rate may slow down; if the amount of the first organic solvent is too small, CNT-OH may agglomerate. In some embodiments, the amount of the first organic solvent relative to each gram of the first product may be 25 to 125 mL. Exemplarily, the amount of the first organic solvent relative to each gram of the first product may be any value selected from 25 mL, 50 mL, 75 mL, 100 mL, and 125 mL, or any value within the range formed by any pair of the above values.
[0054] According to the present invention, in step S2, if the amount of water used is too large, it may result in excessively large polyurethane pores and insufficient product strength; if the amount of water used is too small, it may result in a reduced polyurethane pore structure. In some embodiments, the amount of water used relative to each gram of the first product may be 25 to 125 mL. Exemplarily, the amount of water used relative to each gram of the first product may be any value selected from 25 mL, 50 mL, 75 mL, 100 mL, and 125 mL, or any value within the range formed by any pair of the above values.
[0055] For example, the hydroxide may include at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0056] For example, the oxidant may include at least one of hydrogen peroxide, sodium hypochlorite, and sodium peroxide.
[0057] In some embodiments, the conditions for the oxidation reaction in step S2 may include: an oxidation temperature of 20–60°C and an oxidation time of 6–10 h. For example, the oxidation reaction temperature may be 20°C, 30°C, 40°C, 50°C, 60°C, etc., and the oxidation reaction time may be 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0058] For example, the washing liquid used in the filtration washing process may include at least one of water, ethanol, and acetone.
[0059] In some embodiments, the conditions for the first drying treatment may include: a drying pressure of -0.09 to -0.08 MPa, a drying temperature of 40 to 80°C, and a drying time of 8 to 16 hours. For example, the temperature of the first drying treatment may be 80°C, 85°C, 90°C, 95°C, 100°C, etc., and the drying time may be 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.
[0060] In one embodiment of the present invention, in step S3, the mass ratio of the carbon nanotubes containing hydroxyl groups on the surface, the isocyanate raw material and the diol can be (31-93):(2-10):(87-261).
[0061] According to the present invention, the amount of the second organic solvent used per gram of carbon nanotubes containing hydroxyl groups on their surface can be 4 to 20 mL. Exemplarily, the amount of the second organic solvent used per gram of carbon nanotubes containing hydroxyl groups on their surface can be any value from 4 mL, 5 mL, 10 mL, 15 mL, and 20 mL, or any value within a range formed by any pair of the above values.
[0062] According to the present invention, the amount of water used may be 1 to 5 mL per gram of carbon nanotubes containing hydroxyl groups on their surface.
[0063] For example, the isocyanate raw material may include at least one of toluene diisocyanate, diphenylmethane diisocyanate, and naphthalene 1,5-diisocyanate.
[0064] For example, the diol may include at least one of ethylene glycol, propylene glycol, and butanediol.
[0065] For example, the second organic solvent may include at least one of toluene, xylene, and benzene.
[0066] In some embodiments, the conditions for the second heating reflux treatment in step S3 may include: a heating reflux temperature of 100–120°C and a heating reflux time of 4–10 h. As an example, the temperature of the second heating reflux treatment may be 100°C, 105°C, 110°C, 115°C, 120°C, etc., and the time of the second heating reflux treatment may be 4 h, 6 h, 8 h, 10 h, etc.
[0067] In one embodiment of the present invention, in step S4, if the amount of polytetrahydrofuran raw material is too large, it may result in residues in the product, thereby increasing the resistance and reducing the porosity of the substrate; if the amount of polytetrahydrofuran raw material is too small, it may result in too little product. In some embodiments, the mass ratio of the third product to the polytetrahydrofuran raw material can be (10-40):(0.5-5.5). Exemplarily, the mass ratio of the third product to the polytetrahydrofuran raw material can be any value among 10:0.5, 40:0.5, 10:5.5, and 40:5.5, or any value within the range of any pair of the above values.
[0068] According to the present invention, the amount of the second organic solvent used per gram of the third product can be 1 to 4 mL. Exemplarily, the amount of the second organic solvent used per gram of the third product can be any value selected from 1 mL, 2 mL, 3 mL, and 4 mL, or any value within the range of any two of the above values.
[0069] For example, the polytetrahydrofuran raw material may include at least one of polytetrahydrofuran, poly-2-methyltetrahydrofuran, and poly-2-ethyltetrahydrofuran.
[0070] For example, the second ammonium salt may include at least one of ammonium bicarbonate, ammonium chloride, and ammonium carbonate. Preferred is ammonium bicarbonate, which readily decomposes into ammonia, carbon dioxide, and water upon heating to 60°C. Therefore, in addition to the pores obtained through foaming, the thermal decomposition of ammonium bicarbonate can also form relatively abundant pores inside or on the surface of the polyurethane.
[0071] In some embodiments, the conditions for the polymerization reaction in step S4 may include: a polymerization temperature of 80–120°C and a polymerization time of 8–16 h; the conditions for the second drying treatment may include: a drying pressure of -0.09–-0.08 MPa, a drying temperature of 40–80°C, and a drying time of 10–16 h.
[0072] For example, in step S5, the counter electrode can be a platinum sheet; the reference electrode can be Ag / AgCl.
[0073] In one embodiment of the present invention, the concentration of metal ions in the electrolyte containing metal ions can be 0.1 to 0.9 mol / L. Exemplarily, the concentration of metal ions in the electrolyte containing metal ions can be any value selected from 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, and 0.9 mol / L, or any value within the range formed by any pair of the above values.
[0074] For example, the metal ion may be a copper ion.
[0075] In this invention, if the deposition treatment time is too short, the conductivity of the current collector may deteriorate; if the deposition treatment time is too long, the surface Cu layer may agglomerate, thereby affecting the conductivity of the current collector. In some embodiments, the deposition treatment conditions in step S5 may include: a constant potential of -1.5 to -0.7V and a deposition time of 5 to 15 minutes; exemplaryly, the washing solution used in the washing treatment may include anhydrous ethanol. The conditions for the third drying treatment may include: a drying pressure of -0.09 to -0.08 MPa, a drying temperature of 25 to 45°C, and a drying time of 8 to 16 hours. As an example, the temperature of the third drying treatment may be 100°C, 105°C, 110°C, 115°C, 120°C, etc., and the time of the third drying treatment may be 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.
[0076] A second aspect of the present invention provides a negative electrode current collector, such as... Figure 1 As shown, the negative electrode current collector is prepared according to the method described above;
[0077] The negative electrode current collector includes a porous substrate and a metal layer, wherein the metal layer is disposed on the surface and within the pores of the porous substrate;
[0078] The substrate material includes carbon nanotubes with hydroxyl groups on their surface and polyurethane foam; the carbon nanotubes with hydroxyl groups on their surface and the polyurethane foam are connected by hydrogen bonds.
[0079] The negative electrode current collector of the present invention is a porous and lightweight foamed copper material, which can reduce the weight of the negative electrode sheet and thus improve the energy density of the battery. Applying the negative electrode current collector of the present invention to the battery can reduce the internal resistance of the battery, enhance the cycle performance of the battery, and reduce the safety risks of the battery.
[0080] In this invention, a suitable mass ratio of carbon nanotubes with hydroxyl-containing surfaces to polyurethane foam has the technical effect of reducing the resistance of the foil. As one embodiment of this invention, the mass ratio of the carbon nanotubes with hydroxyl-containing surfaces to the polyurethane foam in the substrate can be (0.02–0.1):1.
[0081] In this invention, a suitable mass ratio of substrate to metal layer can reduce the resistance of the foil and increase the porosity of the substrate. In some embodiments, the mass ratio of substrate to metal layer can be 1:0.2 to 1. Exemplarily, the mass ratio of substrate to metal layer can be any value from 1:0.2, 1:0.4, 1:0.6, 1:0.8, and 1:1, or any value within the range of any pair of the above values.
[0082] In some embodiments, the thickness of the substrate can be 0.004 to 0.12 mm. For example, the thickness of the substrate can be any value among 0.004 mm, 0.01 mm, 0.03 mm, 0.06 mm, 0.09 mm, and 0.12 mm, or any value within the range formed by any pair of the above values.
[0083] In some embodiments, the thickness of the metal layer can be 0.5 to 10 μm. For example, the thickness of the metal layer can be any value selected from 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, and 10 μm, or any value within the range formed by any pair of the above values.
[0084] For example, the material of the metal layer includes copper.
[0085] A third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative current collector prepared according to the preparation method described above, or the negative current collector described above.
[0086] A fourth aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode is the negative electrode described above.
[0087] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0088] Example 1
[0089] (1) Preparation of carbon nanotubes with hydroxyl groups on the surface
[0090] 6g of carbon nanotubes were placed in a reaction vessel, followed by 2.5g of sodium borohydride and 3.5g of ammonium sulfate, and then 250mL of tetrahydrofuran. After mixing in the reaction vessel, the mixture was refluxed at 90℃ for 12 hours and then cooled to room temperature to obtain the first product. 6g of the first product was mixed with 250mL of deionized water, 75mL of tetrahydrofuran, 15mL of hydrogen peroxide, and 5g of sodium hydroxide, and an oxidation reaction was carried out at 40℃ to obtain the second product. The second product was filtered, washed with hot water, then washed with ethanol and acetone, and dried in a vacuum oven at 60℃ for 12 hours to obtain the dried substance, namely carbon nanotubes with hydroxyl groups on their surface, denoted as CNT-OH.
[0091] (2) Synthesis of polyurethane
[0092] 2g of CNT-OH obtained in step (1), 1mol of ethylene glycol, 1mol of toluene diisocyanate (TDI), 10g of deionized water, and 40mL of toluene were added to a reaction vessel and mixed. A second reflux treatment was then performed, with the following conditions: oil bath, temperature 110℃, and time 6h, yielding a third product. 25g of the third product, 3g of polytetrahydrofuran, 40mL of toluene, and 4g of ammonium bicarbonate powder were stirred until homogeneous and then subjected to a polymerization reaction for 12 hours to obtain a precipitate. The precipitate was dried in a vacuum oven at 60℃ for 12h to obtain carbon nanotube-modified polyurethane foam, which can be designated CNT-PU.
[0093] (3) Copper plating on modified polyurethane surface (synthesis of copper foam)
[0094] Using the principle of an electrolytic cell, the modified CNT-PU obtained in step (2) was used as the working electrode, and the platinum sheet and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively. The electrodeposition was carried out in a 0.5 mol / L copper sulfate solution containing sulfuric acid for 600 s at a constant potential of -1.1 V (relative to the Ag / AgCl electrode) to obtain a Cu layer on the surface of the PP film. After the surface was slightly rinsed with anhydrous ethanol, it was vacuum dried at 35 °C for 12 h to obtain foamed copper, which was denoted as Cu / CNT-PU-600.
[0095] (4) Preparation of positive electrode sheet
[0096] Lithium nickel cobalt manganese oxide powder, conductive carbon, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1 to obtain a mixed material. The mixed material is then thoroughly stirred in N-methylpyrrolidone (NMP) to obtain the corresponding positive electrode active slurry. The positive electrode active slurry is coated onto aluminum foil to obtain the first electrode, wherein the mass fraction of lithium nickel cobalt manganese oxide powder in the first electrode is 80wt%. After drying and pressing, the positive electrode is obtained.
[0097] (5) Preparation of lithium-ion batteries
[0098] Ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0099] The foamed copper obtained in step (3) is used as the negative electrode, and the positive electrode and PE separator obtained in step (4) are wound together to obtain the corresponding core. Then, the core is dried, injected with electrolyte, packaged, formed, and tested to obtain a lithium-ion battery.
[0100] Example 2
[0101] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1. The difference is that in step (3), electrodeposition is performed at a constant potential of -1.1V (relative to the Ag / AgCl electrode) for 300s, and the resulting copper foam material is denoted as Cu / CNT-PU-300.
[0102] Example 3
[0103] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1. The difference is that in step (3), electrodeposition is performed at a constant potential of -1.1V (relative to the Ag / AgCl electrode) for 900s, and the resulting copper foam material is denoted as Cu / CNT-PU-900.
[0104] Example 4
[0105] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1, except that in step (2), the amount of CNT-OH added is 0.5g.
[0106] Example 5
[0107] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1, except that in step (2), the amount of CNT-OH added is 3.5g.
[0108] Example 6
[0109] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1, except that in step (2), the amount of deionized water added is 5g.
[0110] Example 7
[0111] The preparation method of the lithium-ion battery in this embodiment is the same as that in embodiment 1, except that in step (2), the amount of deionized water added is 15g.
[0112] Comparative Example 1
[0113] 4.5μm copper foil purchased commercially.
[0114] Comparative Example 2
[0115] The preparation method of the lithium-ion battery in this comparative example is the same as that in Example 1, except that ordinary carbon nanotubes are used instead of CNT-OH in step (2).
[0116] Comparative Example 3
[0117] The preparation method of the lithium-ion battery in this comparative example is the same as that in Example 1, except that ammonium bicarbonate is not added in step (2).
[0118] Test Example 1
[0119] The electrodes prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1.
[0120] Physical performance tests of the electrode:
[0121] (1) Test method for liquid absorption rate: For each group, take a 5×5cm² negative electrode sheet after roller pressing, weigh it and record the weight as a. Soak the electrode sheet in the electrolyte for 1 hour to allow it to fully absorb the electrolyte. After absorption, hang the electrode sheet for 5 minutes to dry the electrolyte adhering to the diaphragm surface, weigh it and record the weight as b. The liquid absorption rate of the electrode sheet is (ba) / a×100%.
[0122] (2) Electrode film resistance test method: Place the electrode in the film resistance test to obtain the film resistance of the corresponding electrode.
[0123] Table 1
[0124] Example 1 139 0.18 Example 2 127 0.23 Example 3 122 0.25 Example 4 121 0.31 Example 5 117 0.34 Example 6 124 0.25 Example 7 121 0.27 Comparative Example 1 / 0.42 Comparative Example 2 109 0.36 Comparative Example 3 103 0.38
[0125] Test Example 2
[0126] The batteries prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 2.
[0127] Battery performance testing:
[0128] (1) Initial Coulombic Efficiency: After the battery is manufactured, it is first charged at a constant current rate of 0.1C to 3.75V to obtain the formation capacity C0. Then the battery is divided into equal parts and charged at a constant current rate of 0.33C to 4.25V, and then charged at a constant voltage of 4.25V until I≤0.05C to obtain the divided battery capacity C1. After standing for 5 minutes, the battery is discharged at a constant current rate of 1C to 2.8V to obtain the discharge capacity C2, then discharged at a constant current rate of 0.1C to 2.8V to obtain the discharge capacity C3, and finally discharged at a constant current rate of 0.01C to 2.8V to obtain the discharge capacity C4. The initial efficiency is calculated as (C2+C3+C4) / (C0+C1)*100%.
[0129] (2) Energy density: First, weigh each battery in the test group to obtain the mass of the battery and record it as m. Then, at 25℃, charge the battery with a constant current of 0.1C to 4.25V, and then charge it with a constant voltage of 4.25V until the current is ≤0.05C. After standing for 5 minutes, discharge it with a constant current of 0.1C to 2.8V to obtain the discharge energy Q. The battery energy density is calculated as Q / m.
[0130] (3) Cycle capacity retention: At 25℃, the battery was first charged at a constant current of 0.5C to 4.25V, and then charged at a constant voltage of 4.25V until the current I ≤ 0.05C. The battery capacity at 0.5C charging was recorded as C0. After standing for 15 minutes, the battery was discharged at a constant current of 0.5C to 2.8V, and the discharge capacity of one cycle was recorded as C1. The discharge capacity of 100 cycles was recorded according to this cycle process. 100 The battery capacity retention rate was obtained after 100 cycles.
[0131] Table 2
[0132]
[0133] As can be seen from Tables 1 and 2, the electrode prepared in the embodiments of the present invention has a significantly improved liquid absorption rate and a significantly reduced film resistance compared with the comparative example; the battery prepared in the embodiments of the present invention has a significantly reduced internal resistance and a significantly improved first-efficiency, energy density and cycle performance compared with the comparative example. Specifically, Examples 1, 2, and 3 alter the electrode properties by changing the copper electrodeposition time. A suitable electrodeposition time is required; a shorter time results in insufficient copper content, inadequate conductivity, increased membrane resistance, and reduced porosity due to thermal decomposition of ammonium bicarbonate, leading to decreased liquid absorption. Conversely, an excessively long deposition time may cause copper agglomeration on the polyurethane, increasing membrane resistance and decreasing liquid absorption. Examples 4 and 5 change the CNT content. Too little CNT, a porous three-dimensional material, may cause insufficient conductivity and decreased liquid absorption; too much may lead to agglomeration, resulting in decreased conductivity and insufficient liquid absorption. Examples 6 and 7 change the internal pore structure of the polyurethane by altering the water content. Too little water reduces porosity, resulting in less copper foil deposition and increased resistance; too much water leads to higher porosity, causing uneven agglomeration of the copper layer, further reducing porosity and increasing membrane resistance.
[0134] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode current collector, characterized in that, The preparation method includes the following steps: S1. Carbon nanotubes, borohydride, first ammonium salt and first organic solvent are mixed and subjected to first heating and reflux treatment to obtain the first product; S2. The first product, water, hydroxide, oxidant and the first organic solvent are mixed and oxidized to obtain the second product; the second product is filtered, washed and dried to obtain carbon nanotubes with hydroxyl groups on the surface. S3. The carbon nanotubes with hydroxyl groups on their surface, isocyanate raw material, glycol, water, and a second organic solvent are mixed and subjected to a second heating and reflux treatment to obtain a third product. S4. The third product, polytetrahydrofuran raw material, the second organic solvent, and the second ammonium salt are mixed and polymerized to obtain a precipitate; the precipitate is subjected to a second drying treatment to obtain carbon nanotube modified polyurethane foam. S5. Using the carbon nanotube-modified polyurethane foam as the working electrode, the working electrode, the counter electrode, and the reference electrode are placed in an electrolyte containing metal ions to carry out a deposition reaction, thereby obtaining a substrate with a metal layer deposited on its surface. The substrate with the metal layer deposited on its surface is then subjected to a washing treatment and a third drying treatment.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the carbon nanotubes, the borohydride, and the first ammonium salt is (2~10):(0.5~4.5):(0.5~6.5). The amount of the first organic solvent used is 25-125 mL relative to each gram of the carbon nanotubes; The borohydride includes at least one of sodium borohydride, potassium borohydride, calcium borohydride, magnesium borohydride, and lithium borohydride; The first ammonium salt includes at least one of ammonium sulfate, ammonium nitrate, ammonium chloride, ammonium bisulfate, ammonium fluoride, ammonium carbonate, and ammonium bicarbonate; The first organic solvent includes at least one of tetrahydrofuran, acetonitrile, formamide, and acetone.
3. The preparation method according to claim 2, characterized in that, In step S1, the conditions for the first heating and reflux treatment include: a heating and reflux temperature of 80~100℃ and a heating and reflux time of 8~16h.
4. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the first product to the hydroxide is (2~10):(1~9). The amount of the first organic solvent used is 25-125 mL relative to each gram of the first product; The amount of water used is 25-125 mL per gram of the first product; The hydroxide includes at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide; The oxidant includes at least one of hydrogen peroxide, sodium hypochlorite, and sodium peroxide.
5. The preparation method according to claim 4, characterized in that, In step S2, the conditions for the oxidation reaction include: an oxidation temperature of 20~60℃ and an oxidation time of 6~10h; the washing liquid used in the filtration and washing process includes at least one of water, ethanol and acetone; the conditions for the first drying process include: a drying pressure of -0.09~-0.08MPa, a drying temperature of 40~80℃, and a drying time of 8~16h.
6. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of the carbon nanotubes with hydroxyl groups on their surface, the isocyanate raw material, and the diol is (31~93):(2~10):(87~261). The amount of the second organic solvent used is 4 to 20 mL per gram of carbon nanotubes containing hydroxyl groups on their surface; The amount of water used is 1 to 5 mL per gram of carbon nanotubes containing hydroxyl groups on their surface; The isocyanate raw material includes at least one of toluene diisocyanate, diphenylmethane diisocyanate and naphthalene 1,5-diisocyanate; The diol includes at least one of ethylene glycol, propylene glycol, and butanediol; The second organic solvent includes at least one of toluene, xylene, and benzene.
7. The preparation method according to claim 6, characterized in that, In step S3, the conditions for the second heating reflux treatment include: a heating reflux temperature of 100~120℃ and a heating reflux time of 4~10h.
8. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of the third product to the polytetrahydrofuran raw material is (10~40):(0.5~5.5). The amount of the second organic solvent used is 1 to 4 mL relative to each gram of the third product; The polytetrahydrofuran raw materials include at least one of polytetrahydrofuran, poly2-methyltetrahydrofuran, and poly2-ethyltetrahydrofuran; The second ammonium salt includes at least one of ammonium bicarbonate, ammonium chloride, and ammonium carbonate.
9. The preparation method according to claim 8, characterized in that, In step S4, the conditions for the polymerization reaction include: polymerization temperature of 80~120℃ and polymerization time of 8~16h; the conditions for the second drying treatment include: drying pressure of -0.09~-0.08MPa, drying temperature of 40~80℃ and drying time of 10~16h.
10. The preparation method according to claim 1, characterized in that, In step S5, The counter electrode is a platinum sheet; The reference electrode is Ag / AgCl; The concentration of metal ions in the electrolyte containing metal ions is 0.1~0.9 mol / L.
11. The preparation method according to claim 10, characterized in that, The metal ion is a copper ion.
12. The preparation method according to claim 10, characterized in that, In step S5, the deposition treatment conditions include: a constant electrical potential of -1.5 to -0.7V and a deposition time of 5 to 15 minutes; the washing solution used in the washing treatment includes anhydrous ethanol; the third drying treatment conditions include: a drying pressure of -0.09 to -0.08MPa, a drying temperature of 25 to 45°C, and a drying time of 8 to 16 hours.
13. A negative electrode current collector, characterized in that, The negative electrode current collector is prepared by the method according to any one of claims 1 to 12; The negative electrode current collector includes a porous substrate and a metal layer, wherein the metal layer is disposed on the surface and within the pores of the porous substrate; The substrate material includes carbon nanotubes with hydroxyl groups on their surface and polyurethane foam; the carbon nanotubes with hydroxyl groups on their surface and the polyurethane foam are connected by hydrogen bonds.
14. The negative electrode current collector according to claim 13, characterized in that, In the substrate, the mass ratio of the carbon nanotubes with hydroxyl groups on their surface to the polyurethane foam is (0.02~0.1):1; The mass ratio of the substrate to the metal layer is 1:0.2~1; The thickness of the substrate is 0.004~0.12mm; the thickness of the metal layer is 0.5~10μm.
15. The negative electrode current collector according to claim 14, characterized in that, The material of the metal layer includes copper.
16. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector prepared by the preparation method according to any one of claims 1 to 12 or a negative current collector according to any one of claims 13 to 15.
17. A battery, characterized in that, The battery includes a negative electrode, wherein the negative electrode is the negative electrode as described in claim 16.
Citation Information
Patent Citations
Method for preparing current collector for lithium battery by sponge template method and current collector
CN118448640A
Composite current collector and application thereof
CN119419280A